Um arcabouço ferramental para implantação personalizável de serviços de rede virtualizados - Garcia, Vinícius Fülber (2019)
The current telecommunication infrastructures rely on the use of network functions implemented in dedicated hardware which are able to identify, handle, modify, and execute many protocols and services. However, difficulties related to the maintenance and upgrade of these dedicated hardwares leads to a process called Internet ossification, limiting the evolution of the Internet. In this context, the Network Function Virtualization paradigm arises as an option to migrate these functions from a dedicated and physical environment to a virtualized one, completely running on commercial off-the-shelf servers and inheriting the flexibility (e.g., monitoring, scale, sharing) typically found in virtualized environments. Thereby, new challenges emerge and are gradually explored by the scientific community to foster the adoption of NFV. Specifically, the deploymment of virtualized network services is composed by three main stages (composition, embedding, and scheduling) whose are named as Network Function Virtualization Resource Allocation. Therefore, diverse solutions were developed to solve specific requirements for single deployment scenarios (e.g., reducing the overall delay, minimizing the fincancial cost, increase the processing units availability) using, for that, particular and application oriented topological and service resquest models. This work, on the other side, proposes a holistic framework containing models, methods and solutions capable to describe and execute deployment process for generic scenarios through customized definitions, without the need to lead with low level processing details or source code modification. The main contribuitions are: a virtualized network service topology specification model; a virtualized network service request generic model; an indexing method applicable to any Network Function Virtualization Resource Allocation stage; and two solutions, one for composition and another for multi-domain embbeding, which use the developed tools. Finally, the framework was evaluated through the experimentation of the developed solutions to a security, content control and load balancing service for HTTP and HTTPS servers. The obtained results showed the the tested solutions’ correct operational behaviour and their results representativity in real instantiations, suggesting the using feasibility of the developed framework.